Relative effects of mammal herbivory and plant spacing on seedling recruitment following fire and mining - Parsons, Michael; Rafferty, Christine; Lamont, Byron; Dods, K.; Fairbanks, Meredith (BioMed Central, 2007)
Background: There is much debate concerning which ecological constraints are the most limiting factors to seedling recruitment in disturbed communities. We provide the first comparison between selective herbivory and plant competition effects among two post-mined forest ecosystems (primary succession) and one post-fire woodland ecosystem (secondary succession). Animal exclosure assessments of nine common species across eight sites were performed for comparison within three locations separated by up to 200 km. Additionally, we asked whether prebrowsed plants differed in nutrient content between or within species in the separate systems.Results: Among the nine common species, seven of these were affected by mammal herbivorywhile five shared a similar vulnerability to predation regardless of system. One species was limited by competition (planting density). There was a strong linear correlation between herbivore selectivity (% browsed) and impact (biomass loss) on the fertilized minesites, but not post-fire sites. Phosphorus and potassium were higher for most species in the post-mined system. Principal components analyses revealed that nutrients in shortest supply may be the most likely components of selection within each system. Among all locations, species with highest levels of phosphorus, ADF and leaf water content were often favoured, while high tannins and nitrogen content were generally selected against.Conclusion: Herbivory, rather than seedling competition, was the limiting factor for plant performance among post-fire and post-mined reclamation areas. The post-fire seedlings were smaller and more water and nutrient limited, nevertheless browsing prevalence was equivalent at all locations with nearly all seedlings predated. Kangaroo density in the post-fire community declined from the beginning of the experiment, while numbers in the post-mined revegetation increased fourfold within one year. Differences in water and nutrient availability may explain why herbivores are more likely to be attracted to post-mined communities.